Application of reduction scenarios on traffic-related NOx emissions in Trabzon, Turkey - KESKİN, SIDDIK SİNAN (TURKISH NATL COMMITTEE AIR POLLUTION RES & CONTROL-TUNCAP, 2020)
Traffic-related emissions are the main sources of certain air pollutants that affect large number of people in many city centers. Because of this fact, quantification of traffic-related emissions and their dispersion modeling are required to determine human exposure to these pollutants. In this study, the most populated Ortahisar district of Trabzon, a city located in the Eastern Black Sea region of Turkey, was selected as the study area since high traffic density is known to be one of the major sources of air pollution in this district. Moreover, air quality measurement stations located close to major roads are available to provide experimental data for model validation. Traffic emission inventory for some pollutants (NOx, SO2, CO, PM and VOCs) was prepared. Considering that NOx is the most representative air pollutant of road traffic emissions, its inventory together with topographical properties and meteorological conditions were used in AERMOD dispersion model to calculate NOx concentrations at selected receptor points. For validation, model data were compared to measurement data by certain statistical tools. According to the model results, 10.1% of the population living in Ortahisar district was exposed to traffic-related NOx concentrations higher than the regulatory limit value. In the study, five different emission reduction scenarios were tested to observe the effects on the exposure levels. Model results indicated that the measures represented by these scenarios are capable of reducing exposure levels between 2.4 and 99.5 percent.
Keywords: Road traffic; NOx pollution; Modeling; Clean air action plans; Population exposure; AIR-POLLUTION; IMPACT; DISPERSION; POLLUTANTS; VALIDATION; EXPOSURE; MODEL